2014
DOI: 10.1120/jacmp.v15i1.4308
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atherosclerotic plaque: a contrast‐detail study using multidetector and cone‐beam computed tomography

Abstract: A Hindmarsh‐Rose model perceptibility phantom containing inserts with various in vitro atherosclerotic plaque compositions was constructed and imaged on a clinical 64 slice multidetector (MDCT) system using 80 and 120 kVp settings and two other cone‐beam (CBCT) systems at 80 kVp. Perceptibility of the simulated lipid‐fibrotic plaque solutions in the images was evaluated by six observers. The effective doses of the protocols employed were estimated using phantom CTDI‐vol measurements placed at identical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The results presented in this research prove that the conventional form of the CDRAD can be extended to include various ranges of attenuating materials filling the holes instead of only using air. It has also been recently identified that conversion of a typical CDP into a low-contrast form has been considered highly valuable radiologically [11]. The findings from this research similarly suggest that using a modified form of the CDP for projection imaging systems will be a valuable addition to radiology departments.…”
Section: Resultssupporting
confidence: 52%
“…The results presented in this research prove that the conventional form of the CDRAD can be extended to include various ranges of attenuating materials filling the holes instead of only using air. It has also been recently identified that conversion of a typical CDP into a low-contrast form has been considered highly valuable radiologically [11]. The findings from this research similarly suggest that using a modified form of the CDP for projection imaging systems will be a valuable addition to radiology departments.…”
Section: Resultssupporting
confidence: 52%
“…Studies show that the quality of carotid atherosclerosis visualization by conventional CT does not differ from that of CBCT [11,12]. A study that evaluated the incidence of extracranial calcifications in course of ICA (ExCICA) and intracranial calcification in ICA (InCICA) on cone beam computed tomography scans shows that the possibility of detectable ExCICAs and InCICAs increases with increasing age; this is more prominent for InCICAs.…”
mentioning
confidence: 99%